Teacher education encounters climate change and critical mathematics education - Magnus Ödmo; Lisa Björklund Boistrup; Anna Chronaki (Prometeica)
In this study we discuss the complexity faced by a teacher when Critical Mathematics Education (CME) and climate change are being brought into a specific teaching setting that is part of a teacher education program a large university in Sweden. Taking CME and Active Network Theory into account along with the teacher’s dilemmas, we here perform an inquiry that aims to map potential actants and their relationships, as they are core in a teacher’s experience to plan and enact a statistics course that engages the theme of climate change through CME. For this inquiry, the teacher’s log (or course diary notes) is analysed. The analysis locates instances where the teacher connects to different actants such as the climate change phenomenon, the curricula, the course plan, and student teachers. In some instances, these actants suggest ways of doing that contradict each other. In short, the analysis shows that since diverse arguments can be narrated, one might be left with the feeling of missing something in just following one. It is a rather vulnerable situation the teacher is in; risking being hold accountable for not dealing with the mathematical content that has good arguments for it to be dealt with, but, yet, knowing that taking this risk allows mathematics to enter the social.